2021
DOI: 10.1097/ju.0000000000001576
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Anti-PD-1 Immune Checkpoint Inhibition Treats Urothelial Bladder Cancer in a Mouse Model

Abstract: Purpose:Nonmuscle-invasive bladder cancer is treated by resection within the bladder and bladder instillment with bacillus Calmette-Guérin or chemotherapy. For bacillus Calmette-Guérin-refractory disease, systemic anti-PD-1 (programmed cell death protein 1) immune checkpoint inhibition is a treatment. Our aim is to test whether intravesical instillment with anti-PD-1 inhibitor treats localized bladder cancer as effectively as systemic administration.Materials and Methods:We investigated an orthotopic mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Local immunotherapy administration into the bladder could represent a substantial clinical benefit, reducing systemic exposure and side effects. Our study in rats and the study reported by Kirschner et al [38] in mice are encouraging in this respect. However, additional clinical trials are warranted before intravesical instillation of anti-PD-L1 could be widely used in humans alone or in combination with HAL and BL.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Local immunotherapy administration into the bladder could represent a substantial clinical benefit, reducing systemic exposure and side effects. Our study in rats and the study reported by Kirschner et al [38] in mice are encouraging in this respect. However, additional clinical trials are warranted before intravesical instillation of anti-PD-L1 could be widely used in humans alone or in combination with HAL and BL.…”
Section: Discussionsupporting
confidence: 85%
“…A recent study of Kirschner et al compared efficacy of intravesical versus systemic (intraperitoneal) administration of an anti-PD-1 inhibitor in the treatment of localized bladder cancer in an orthotopic mouse model [38]. Intravesical anti-PD-1 administration had trend to improved survival thus providing effective anti-tumor treatment for bladder tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, six once-weekly administrations of intravesical anti-PD-1 treatment had a very high rate of clearing bladder tumours (nearly 100% in most cohorts) [6].…”
Section: Discussionmentioning
confidence: 87%
“…In our previous study, six once‐weekly administrations of intravesical anti‐PD‐1 treatment had a very high rate of clearing bladder tumours (nearly 100% in most cohorts) [6]. In the present study, we tested if only one intravesical instillation of anti‐PD‐1 treatment and/or reovirus would be sufficient to treat bladder tumours.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, a novel approach for ICI therapy was recently presented. In SUBDUE-1, a dose-finding phase 1b trial, intravesical injection of durvalumab is under investigation for patients with NMIBC [39], an approach that has shown promising results in the pre-clinical studies [40].…”
Section: B2b: Bladder Cancer Summarymentioning
confidence: 99%